Isolation and Cloning of mercuric reductase gene (merA) from mercury-resistant bacteria - Parisa Khoshniyat; Alireza Tarinejad; Mohammad Pazhang (Biological Journal of Microorganism, 2018)
Introduction: Some of the bacteria having merA gene coding mineral mercury reducing enzyme, has genetic potential of Hg removing via reduction of mineral mercury and transformation of that to gas form and finally bioremediation of polluted area. The aim of this study is the isolation of merA gene from resistance bacteria and cloning of that into suitable expression vector and then the environmental bioremediation by the transformation of bacteria with this vector. Materials and methods: A number of bacteria were collected in contaminated areas with mercury in order to isolate merA genes. Polymerase chain reaction had done on the four bacterial genomes including Klebsiella pneumoniae, Pseudomonas aeruginosa, Serratia marcescens and Escherichia coli using the specific primers in order to detect merA gene. For cloning, the primers containing restriction enzyme sites are used, merA gene was isolated and amplified. The amplified fragments were cloned in the expression vector pET21a+ and via heat shock method were transformed into E. coli TOP10 competent cell. For clustering of genes, Mega software version 4 was used and bioanformatic studies were achieved for predicted enzyme. Results: merA gene with 1686 bp in length was isolated from K pneumoniae and E. coli. Recombinant vectors in transgenic bacteria were confirmed by various methods and finally were confirmed by sequencing. The result of clustering these genes with existence genes in NCBI showed high similarity. Discussion and conclusion: The existence of merA gene in bacteria that adapted to Hg pollution area is because of resistance, so with cloning this gene into suitable expression vector and transformation of susceptible bacteria with this vector ability of resistance to Hg in bacteria for bioremediation could be given.